Hydrocarbon Charge History of the Upper Paleozoic, Ordos Basin as Revealed by Fluid Inclusions - Cao, Qing; Wei, Xinshan; Chen, Zhangxing; Zhao, Jingzhou; Tang, Mingju (Frontiers in Physics, 2022)
The petrographic characteristics of fluid inclusions of the main gas-bearing intervals of the Upper Paleozoic in the Ordos Basin are analyzed by means of plane-polarized light, fluorescence microscopy, and microthermometry. With the burial history of the basin, the charging and enrichment of natural gas in low-permeability reservoirs are also studied through a comparison of parameters such as the homogenization temperature and freezing temperature of aqueous inclusions associated with hydrocarbon inclusions. A comprehensive analysis of the assemblage characteristics, components, and temperature of fluid inclusions of the Upper Paleozoic shows that the abundance, attitude, and composition of gaseous hydrocarbon inclusions can reflect petroleum enrichment in low-permeability reservoirs. The homogenization temperature and freezing temperature of aqueous inclusions associated with gaseous hydrocarbon inclusions show no obvious discontinuities, indicating that natural gas charging was a long and continuous process since the Late Triassic to Early Cretaceous (210–100 Ma) and natural gas accumulation mainly occurred during the Early Cretaceous (125–100 Ma).